The Role of Profitability in Mediating the Effect of Capital Structure and Liquidity on Firm Value in Food and Beverage Sub-Sector in Indonesian Stock Exchange - Putu Dyah Pradnya Paramitha (Jurnal Ekonomi & Bisnis JAGADITHA, 2020)
This study aims to analyze the significance of the capital structure and liquidity effect on the profitability value, to analyze the significance of the capital structure, liquidity and profitability effect on firm value, and to analyze the role of profitability in mediating the capital structure and liquidity effect on firm value. The population in this study is food and beverage companies in Indonesia Stock Exchange. The sample was conducted by purposive sampling method and then the number of samples is 12 companies. The research data is secondary data obtained from the website of the Indonesia Stock Exchange and the Indonesia Capital Market Directory from 2013 until 2016. Data analysis is by path analysis technique with IBM SPSS Statistic Version 22. The results of this study showed that: (1) the capital structure negative, not significant impact on profitability. (2) the liquidity had negative significant impact on profitability. (3) the capital structure had negative significant impact on firm value. (4) the liquidity had a negative not significant impact on firm value. (5) the profitability had a positive and significant impact on firm value. (6) profitability is able to mediate the effect of capital structure on firm value significantly. (7) profitability is able to mediate the effect of liquidity on firm value significantly.